Microbial control during the incubation of rainbow trout (Oncorhynchus mykiss) eggs exposed to humic acid - Chiasson, Marcia; Kirk, Michael; Huyben, David (Frontiers in Aquaculture, 2023)
Introduction Cultured fish species are increasingly exposed to fungi and bacteria in the rearing environment, often causing disease and mortality causing aquaculture producers to rely on the use of chemical therapeutants which may have negative consequences for both human and environmental health. This study investigated the effect of humic acid as a treatment to reduce fungal and bacterial infections to increase survival during the incubation of rainbow trout (Oncorhynchus mykiss) eggs. Methods Humic acid, an aqueous extract of oxidized lignite was added to water entering both stacked tray and jar type incubators at a dosage rate of 5 mg/L from fertilization until hatching. Results The water treatment eliminated observable fungus and significantly improved survival until hatching in the treated incubator trays (77.2%) compared to the untreated controls (55.5%) (p ≤ 0.001). Egg survival was not improved in the incubator jars. The humic acid reduced bacterial diversity, but only in the stacked tray incubators and altered bacterial composition of the water after 20 days of treatment. Discussion The treatment increased the bacterial abundance of Burkholderiales, positively associated with healthy fish eggs and decreased the abundance of Flavobacterium and Aeromonas, known fish pathogens. These findings support the topical treatment of humic acid as a potential alternative treatment to prevent fungal infections and reduce mortality during incubation of rainbow trout eggs.